Oral delivery of therapeutic proteins by engineered bacterial type zero secretion system - Xu Gong; Shan Liu; Bozhang Xia; Yichen Wan; Shuyi Zhang; Baoyan Zhang; Zehao Wang; Junge Chen; Fei Xiao; Xing-Jie Liang; Yun Yang (Nature Communications)
Abstract Genetically engineered commensal bacteria are promising living drugs, however, their therapeutic molecules are frequently confined to their colonization sites. Herein, we report an oral protein delivery technology utilizing an engineered bacterial type zero secretion system (T0SS) via outer membrane vesicles (OMVs). We find that OMVs produced in situ by Escherichia coli Nissle 1917 (EcN) can penetrate the intact gut epithelial barrier to enter the circulation and that epithelial transcytosis involves pinocytosis and dynamin-dependent pathways. EcN is engineered to endogenously load various enzymes into OMVs, and the secreted enzyme-loaded OMVs are able to stably catalyze diverse detoxification reactions against digestive fluid and even enter the circulation. Using hyperuricemic mice and uricase delivery as a demonstration, we demonstrate that the therapeutic efficacy of our engineered EcN with a modified T0SS outperforms that with a direct protein secretion apparatus. The enzyme-loaded OMVs also effectively detoxify human serum samples, highlighting the potential for the clinical treatment of metabolic disorders.